China–Pakistan Economic Corridor: The Geo‐Strategic Dimension and Challenges - Mr. Majid Mahmood (CISS Insight Journal, 2015)
The geographical location of a country determines its role in the world politics. It denotes that how critically beneficial or non‐beneficial is the country to the other countries in social, economic and political respects. Pakistan is located at a very strategically important place on the globe. It is situated at the juncture of energy proficient to energy deficient countries. The geo‐strategic importance of Pakistan is also evident from the fact that it is surrounded by world’s emerging economic giants; i.e. India and China, and countries rich in natural resources; i.e. Afghanistan and Iran. China and Pakistan have developed strong bilateral trade and economic ties and cooperation over the years. China has gradually emerged as Pakistan’s major trading partner both in terms of exports and imports. Bilateral trade and commercial links between the two countries were established in January 1963 when both signed the first bilateral long‐term trade agreement. Under the Free Trade Agreement (FTA) between the two countries – signed on November 24, 2006 and implemented from July 1, 2007 – Pakistan secured market access for several products of immediate export interest. Later, both countries signed the FTA on Trade in Services on February 21, 2009 that became operational from October 10 that year.